Sustainable infrastructure development: definition of criteria and quantification of indicators for water and wastewater systems in Douro and Trás-os-Montes - Danko, Cristina Carvalho (2008)
Dissertação de mestrado em Engenharia Civil ( área de Especialização Engenharia Municipal)